1991
DOI: 10.1557/proc-238-727
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth Behaviour Of Nanocrystalline Nickel

Abstract: The thermal stability of electrodeposited nanocrystalline Ni-1.2%P and Ni-0.12%S alloys is evaluated by in-situ electron microscopy studies. Isothermal grain size versus annealing time curves at 573K and 623K show an unexpected thermal stabilization in form of a transition from rapid initial grain growth to negligible grain growth. This behaviour is discussed in terms of the various grain boundary drag mechanisms which may be operative in these alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…An earlier in situ TEM annealing study of electrodeposited nanocrystalline Ni [9] reported very different annealing behaviour from that presented in Fig. 3.…”
Section: Eventmentioning
confidence: 64%
See 4 more Smart Citations
“…An earlier in situ TEM annealing study of electrodeposited nanocrystalline Ni [9] reported very different annealing behaviour from that presented in Fig. 3.…”
Section: Eventmentioning
confidence: 64%
“…3. In that study, 10 nm starting grain size Ni was annealed at 573 K for a period of 20.5 h; the grain size increased from the 10 nm starting size to ∼30 nm after 90 min, and stabilized at that size through the remaining 1140 min of the experiment [9]. It is likely that a thin foil effect was responsible for this stabilizing behaviour, considering that it has not been observed in any bulk ex situ annealing experiment of nanocrystalline Ni produced by the same synthesis method (e.g.…”
Section: Eventmentioning
confidence: 99%
See 3 more Smart Citations